Multimedia Security 2: Biometrics, Video Surveillance and Multimedia Encryption - Puech (Wiley Data and Cybersecurity, 2022)
Monograph
fulltext
Keywords: Bioengineering; Communication, Networking and Broadcast Technologies; Components, Circuits, Devices and Systems; Computing and Processing